Islamic And Criminal Law Review About Infaq Distribution Using Charity Boxes On The Road Traffic - Rijal Fahmi (Proceeding International Seminar of Islamic Studies, 2019)
Distribution of infaq using charity boxes on the road traffic room in the context of construction or renovation of houses of worship is increasingly being done by people in the middle of the highway along with the dense traffic flow which can certainly disrupt smooth and safety for road users. The purpose of this study is to examine how the existence of charity boxes in the middle of the road in terms of Islamic law and criminal law based on Law Number 22 Year 2009 concerning Road Traffic and Transportation and Law Number 38 Year 2004 concerning Roads. Through normative juridical research, it was concluded that the distribution of infaq using charity boxes on the road traffic hall is prohibited in Islamic law and even constitutes a violation in criminal law which can make the culprit punished.